SDWG Progress Report to SAO meeting Fairbanks, March 2016. - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group (SDWG), 2016)
Arctic Council working group Sustainable Development Working Group (SDWG)s progress report. Submitted to the Arctic Council's Senior Arctic Officials meeting in Fairbanks, USA, March 16-17, 2016.